Peningkatan Pengetahuan Siswa terhadap Bahaya Kecanduan Pornografi - Dian Sari; Rita Gusmiati; Aulia Khaira Nisa; Fadlulrahman Yaafin; Wiwit Fitria; Ocha Geovani Fransiska; Pita Askia; Irvi Saras Wati; Ratna Novita Sari; Taufik Rahman; Dea Maftahra (Universitas Pahlawan Tuanku Tambusai, 2026)
Exposure to pornography among adolescents can negatively affect mental health, behavior, and academic performance, highlighting the need for preventive health education. This community service program aimed to improve students' knowledge and awareness of the dangers of pornography addiction and its prevention among students at MTI Tarusan Kamang. The program was conducted through health education using PowerPoint presentations, flyers, and interactive discussions. Program effectiveness was evaluated using identical pretest and posttest questionnaires. The results showed an improvement in students' knowledge, with the mean score increasing from 55 on the pretest to 82 on the posttest. Participants also demonstrated high enthusiasm and a better understanding of the harmful effects of pornography and the importance of responsible internet use. Health education proved effective in improving students' knowledge and should be implemented continuously through collaboration among schools, families, and communities to prevent pornography addiction among adolescents.